PERANCANGAN PROTOTYPE HOME AUTOMATION MENGGUNAKAN ARDUINO BERBASIS FEEDBACK SYSTEM - Suryo, Alif; Rosiska, Evan (Computer Science and Industrial Engineering, 2021)
At this time the development of technology is very rapid in providing services to the community to carry out daily life briefly and easily. with the automatic door can make it easier for people to apply it into their homes. to get comfort and security in the house, home automation system is made, namely an automatic home system that can help make it easier for users to establish security in the house. Microcontroller has become the most important part in processing and processing data in a work system. an example of developing a microcontroller, namely the Arduino Uno, is a device that has a board with 14 digital input and output pins. where 6 pins can be used as PWM outputs and 6 inputs can be used as analog. RFID is a technology that uses wireless and has a chip, the chip has an ID number, the ID number can retrieve data and store data from a certain distance. testing is done using an ultra sonic sensor, with an ultra sonic sensor the feedback system can work perfectly. The results obtained from this test are the use of ultra sonic sensors to work well in providing system feedback to users.